Direct contact resistance measurement during thermoelectric testing - Soldatov, A.I.; Soldatov, A.A.; Abouellail, A.A.; Kostina, M.A. (Karagandy University of the name of acad. E.A. Buketov, 2024)
The article analyzes the influence of the contact resistance of the electrodes on the inspection result. It is shown that as the value of the measuring resistor increases, the permissible value of the contact resistance of the electrodes with the test sample increases. An indirect method for monitoring contact resistance has been proposed, which consists of passing a stable high-frequency current through the contact resistance and measuring the voltage across this resistance. The variation of relative voltage across the measuring resistor with respect to the total contact resistance has been graphed. The maximum allowable contact resistance has been determined to ensure that the measured thermoelectric EMF differs from the true value by no more than 10%. The proposed method allows to measure contact resistance directly in the process of monitoring thermoelectromotive force.
Keywords: thermoelectromotive force; hot electrode; cold electrode; contact resistance; current generator; filter; measuring resistor